2016
DOI: 10.1038/srep28884
|View full text |Cite
|
Sign up to set email alerts
|

Wheat CBL-interacting protein kinase 25 negatively regulates salt tolerance in transgenic wheat

Abstract: CBL-interacting protein kinases are involved in plant responses to abiotic stresses, including salt stress. However, the negative regulating mechanism of this gene family in response to salinity is less reported. In this study, we evaluated the role of TaCIPK25 in regulating salt response in wheat. Under conditions of high salinity, TaCIPK25 expression was markedly down-regulated in roots. Overexpression of TaCIPK25 resulted in hypersensitivity to Na+ and superfluous accumulation of Na+ in transgenic wheat lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 56 publications
(63 reference statements)
1
20
0
Order By: Relevance
“…Furthermore, the transmembrane Na + /H + exchange was impaired in the root cells of transgenic wheat. These results suggested that TaCIPK25 negatively regulated salt response in wheat [198].…”
Section: Physiological Roles Of Cbls and Cipks In Plant Responses To mentioning
confidence: 75%
See 1 more Smart Citation
“…Furthermore, the transmembrane Na + /H + exchange was impaired in the root cells of transgenic wheat. These results suggested that TaCIPK25 negatively regulated salt response in wheat [198].…”
Section: Physiological Roles Of Cbls and Cipks In Plant Responses To mentioning
confidence: 75%
“…Under conditions of high salinity, TaCIPK25 expression was markedly down-regulated in wheat roots [198]. Overexpression of TaCIPK25 resulted in hypersensitivity to Na + and superfluous accumulation of Na + in transgenic wheat lines.…”
Section: Physiological Roles Of Cbls and Cipks In Plant Responses To mentioning
confidence: 96%
“…Similarly, considering LSGs 16 genes are involved in response to stress, of these 5 genes associated with oxidative stress and 5 genes of salt stress indicating their high effects on LZFWGs. The major genes response to salt stress are S-adenosylmethionine synthase, BAG family molecular chaperone regulator 4 and Nitrogen regulatory P-II homolog and to oxidative stress named as tocopherol chloroplastic, Peroxidase A2, CBL-interacting protein kinase and chloroplastic lipocalin [Goldgur et al 2007; Jin et al 2016]. Likewise, 10 up-regulated genes are mainly encoding HSPs and associated proteins to respond to heat stress [Gupta et al, 2015].…”
Section: Resultsmentioning
confidence: 99%
“…Number of proteins of CBL-interacting kinase, serine threonine kinase and wall-associated receptor kinase and Mitogen-activated kinase family were highly expressed wheat, involved in metal ion binding and its transportation serine/threonine kinase signalling, protein phosphorylation and response to stresses [Jin et al, 2016; Mao et al,2009; Shi et al, 2018 Hou et al, 2005; Kanneganti et al, 2008; Kumar et al, 2018; Wimalasekera et al, 2018]. Glutathione peroxidase and peroxidase family proteins expression indicates higher response to oxidative stress, glutathione peroxidase activity, metal ions binding & transportation activity [Alzahrani et al 2018; Martinez et al, 2018].…”
Section: Discussionmentioning
confidence: 99%
“…Among these genes, Gh_D10G1882 and Gh_D10G1888 were preferentially expressed and Gh_D10G1874 had higher expression at 3 h ( Figure 4B ). The above three genes were annotated as peroxidase, E3 ubiquitin-protein ligase gene and CBL-interacting protein kinase, respectively, which were involved and functioned in plant responses to salt stress ( Yee and Goring, 2009 ; Jin et al, 2016 ).…”
Section: Resultsmentioning
confidence: 99%